The role of the enteric microbiota in T cell differentiation - Littman, Dan (Henry Stewart Talks, 2011)
Interaction of the microbiomes with the immune system, T helper cell differentiation in response to innate immune system cytokines, Effects of IL-17, IL-17F and IL-22, Balance of inflammatory and regulatory T cells in the intestine, Retinoic Acid Receptor (RAR), Related Orphan Nuclear Receptor, Transfer colitis model, Commensal bacteria and T cell balance in the intestine, Lamina propria, Segmented filamentous bacteria, Does colonization with SFB provide protection from pathogenic microbes?, Does colonization with SFB influence TH17-mediated autoimmune disease?, SFB induction of TH17 cells